Kinerja Karyawan Ditinjau Dari Kecerdasan Emosional dan Pelatihan Kerja pada PT. Adi Sarana Arma, Tbk - T.M Adriansyah (Mahesa Research Center, 2021)
This study aims to determine Employee performance assessed from emotional intelligence and vocational training at PT. Adi Sarana Arma, Tbk the number of samples in this study were 113 respondents. Based on the results of the t test can be seen in t arithmetic on the emotional intelligence variable of 4.899 greater than t table of 1.658 with a probability t of sig 0,000 smaller than the small significance of 0.05. Based on these values, the positive and significant emotional intelligence variables on the performance variable. In the human resource planning variable of 5.402 greater than t table of 1.653 with a probability of t of sig 0,000 smaller than the significance requirement of 0.05, the training variable partially has a positive and significant influence on the performance variable. Based on the results of the F test, the calculated F value is 48.572> 3.08 with sig 0,000 <0.05, indicating that Ho is rejected and Ha is accepted, means that emotional intelligence and job training are appropriate and positive for performance variables. The value of R Square obtained is 0.459 to see the size of the independent variable on the variable by calculating the coefficient of determination (KD) = R2 x 100%, so that KD = 45.9% is obtained. A value of 45.9% performance (participation variable) can be determined by emotional intelligence and job training. The remaining 54.1% is determined by other factors not approved in this study.